PRICE DETERMINANTS OF THE CARBON EMISSION ALLOWANCES IN THE EU EMISSIONS TRADING SYSTEM - Kovacevska, S; Jovanovski, Kiril (Varazdin Development and Entrepreneurship Agency, 2023)
As a consequence of the climate changes occurring at the global level, an international consensus has been reached to limit the global average temperature. To achieve the targets, in 2005 the Emissions Trading System of the European Union (EU ETS) was established, which limits the emission of carbon. Considering the crucial role of this system and its impact on a large number of social entities, the need for an analysis of the entire system appears. Furthermore, the focus in the Europe economy is set on power and heat generation, energy-intensive industrial sectors, and aviation. The goal of the paper is to determine the factors that affect the fluctuations of carbon allowance prices. The paper begins with a relevant literature review, followed by an analysis of the fluctuation of allowance prices in the system. The authors set up econometric models of Autoregressive Distributed Lag (ARDL)/bound test and Var Granger test to examine the impact of selected variables both defined as energy variables and economic activity, on the allowance price in the short- and long-term. The results of the analysis suggest that within the group of the energy variables, only natural gas has a statistically significant impact on the allowance price, while in the economic activity group variables, a significant impact is found with the indicator of economic sentiment, industrial production, and the S600 index. In the end, the authors give recommendations for further research and possible policy activity regarding the stronger carbon emissions reducion.
Keywords: Allowance price, ARDL model, Carbon emissions, EU ETS